Giant saphenous vein graft pseudoaneurysm: treatment with a vascular occlusion device - Ayub, Bilal (Oxford University Press, 2012)
We report the case of a 74-year old male who was evaluated for progressively enlarging right heart border on serial chest radiographs. Computed tomography of the chest revealed a pseudoaneurysm arising from the saphenous vein graft (SVG) to the posterior descending artery with mass effect on the right atrium. Coronary angiography showed severely compromised distal flow and an angiographically small territory at risk. Using a minimally invasive, catheter-based approach, an Amplatzer Vascular Plug II occlusion device was utilized successfully for embolizing the SVG pseudoaneurysm.